Charcoal Rot of Strawberries Caused by Macrophomina phaseolina - Natalia A. Peres; James C. Mertely (EDIS)
PP 242, a 2-page illustrated fact sheet by N.A. Peres and James C. Mertely, describes this new crown-rot disease in Florida -- causal agent and symptoms, disease development and spread, and control. Published by the UF Department of Plant Pathology, November 2007.